Cigarette smoking and smokeless tobacco use among male south Asian migrants in the United Arab Emirates: a cross-sectional study - Raghib Ali; Tom Loney; Mohammed Al-Houqani; Iain Blair; Faisal Aziz; Salma Al Dhaheri; Iffat El Barazi; Elpidoforos S. Soteriades; Syed M. Shah (BMC, 2020)
Abstract Background Few data were available on smoking and smokeless tobacco use in South Asian migrants in the United Arab Emirates (UAE). This study aimed to identify the prevalence and correlates of cigarette smoking and smokeless tobacco use in male South Asian migrants in the UAE. Methods We used a cross-sectional study to recruit a random representative sample of male South Asian migrants, including Indian (n = 433), Pakistani (n = 383) and Bangladeshi (n = 559) nationalities. We used multivariable logistic regression analysis to identify significant correlates of cigarettes smoking and smokeless tobacco use. Results 1375 South Asian migrant adult males participated in the study (response rate 76%) with a mean age of 34 years (SD ± 10). The overall prevalence of cigarette smoking was 28% (95%CI 25-30%) and smokeless tobacco use was 11% (95%CI 10-13%). The prevalence of current cigarette smoking was 21, 23, and 37% among participants from India, Pakistan and Bangladesh, respectively. The prevalence of current smokeless tobacco use was 6, 12, and 16% for Indian, Pakistani, and Bangladeshi participants, respectively. Among study participants, Bangladeshi nationality, hypertension, and alcohol use were significant correlates of current cigarette smoking. Significant correlates of smokeless tobacco use included increased age, less than college level education, alcohol use, and Pakistani or Bangladeshi nationality. Conclusions Current smoking and smokeless tobacco use in South Asian migrants represent a significant public health burden in the UAE. Effective public health measures are needed to reduce tobacco use in this migrant population.